2022
DOI: 10.3390/ijerph19148442
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Effects of Tourism Development on Air Pollution: Evidence from the Panel Smooth Transition Regression Model

Abstract: Based on the theoretical framework of the Environmental Kuznets Curve (EKC), this study investigates whether tourism development can decrease air pollution. This study applies the panel smooth transition regression approach and panel data for 2005–2019 from 283 prefecture-level cities in China to examine the nonlinear effect of tourism development on PM2.5, emissions. Our results reveal that the effects of tourism on PM2.5, emissions vary according to the modes of tourist arrivals. At the national level, the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…The obtained results constitute a significant contribution to the knowledge about the factors influencing students' career perceptions in T&H [82,84,85,92], offering a new perspective on understanding the employment aspirations in tourism through the prism of very timely topics, namely the problem of air pollution and its negative consequences increasingly experienced by societies around the world and seriously threatening tourism development, which is strongly dependent on environmental quality. This paper draws attention to the fact that problems arising from air pollution can affect residents [93] and tourists visiting a particular destination [6,14,16] but may also influence its labour market, decreasing its attractiveness in the eyes of future qualified workforce.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The obtained results constitute a significant contribution to the knowledge about the factors influencing students' career perceptions in T&H [82,84,85,92], offering a new perspective on understanding the employment aspirations in tourism through the prism of very timely topics, namely the problem of air pollution and its negative consequences increasingly experienced by societies around the world and seriously threatening tourism development, which is strongly dependent on environmental quality. This paper draws attention to the fact that problems arising from air pollution can affect residents [93] and tourists visiting a particular destination [6,14,16] but may also influence its labour market, decreasing its attractiveness in the eyes of future qualified workforce.…”
Section: Discussionmentioning
confidence: 99%
“…As is pointed out, tourism can be a source of the same types of pollution as any other industry, including emissions of air pollution, noise, litter, release of industrial and municipal sewage, chemicals, and even architectural/visual pollution [94,96,97]. There are also voices that emissions of air pollution induced by tourism are greater than from other service sectors [6]. Therefore, tourism development may damage the natural environment, and the results of previous studies revealed that there is a link between the intensity of tourist traffic and the level of air pollution with PM 10 [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The extension of this analysis has led to testing the tourism-EKC hypothesis (a systematic review is performed by Sun et al 2022). For the most part, the dependent variable of the analysis has been CO 2 emissions, and less frequently some air pollutants (as in Ciarlantini et al 2023 andZhang andLu 2022). However, in this context, the energy variable has not been previously used.…”
Section: The Model and Main Hypothesis Of The Studymentioning
confidence: 99%
“…Although it is believed that in rural areas and small cities the pollutants concentrations are much lower than in metropolitan cities, this is not always true. The transportation of polluted air masses from nearby large urban areas (Triantafylllou et al, 2016), the seasonal increase of the population (e.g., touristic period, Zhang and Lu 2022) and thus the emissions from traffic and shipping, physical phenomena (e.g., Sahara dust events) and the types of fuel used for residential heating are among the parameters that can negatively affect the local air quality. The existence of a low-cost network of air quality sensors that operate on a daily basis can provide an insight of the conditions that influence the recorded concentrations (Kosmopoulos et al, 2022).…”
Section: Introductionmentioning
confidence: 99%